The impact of asian crisis on Malaysia's foreign direct investment / Nur Firas Nazim - Nazim, Nur Firas (Faculty of Business Management, 2018)
Foreign direct investment has been one of the elements that play the role as the largest contributors to the success of a country over the past few decades. Malaysia has been a part of the developed countries with growing inflow of foreign direct investment (FDI). Malaysia has made a lot of diplomatic relationships as an initiative to increase the business opportunity for the country to expand in various sectors to ensure that their performance could be at par with other developed countries. However, in 1997, Malaysia was struck by the financial tsunami that began with Thailand as the first country that had been affected through its baht devaluation that been considered as the main factor that contributed to ASEAN financial crisis. Malaysia also has been affected from the crisis by experiencing a drop in its foreign direct investments' performance. Most of the investors even started to change their investments' direction to a more stabilized economic countries. Thus, this study is aim to investigate the impact of pre and post Asian financial crisis 1997 on Malaysia's foreign direct investment. The context of Asian crisis in this research refers to the indicators that are used as a reference to conduct the study namely the inflation rate, exchange rate, gross domestic product rate, import, export as well as reserves and savings. From the indicator used, it will help to identify the most significance predictor factor for the crisis as well as to give signal for the government and financial analyst in order to avoid another strike in the future. This research employed a time series data from the year 1982 to 2016. Since this paper would like to identify the impact, therefore, the period before and even after the crisis is taken into considerations. The results had also come to a conclusion that inflation, exchange rate, gross domestic products, import, exports, reserves and savings which act as the proxies for Asian crisis are negatively related to foreign direct investments in Malaysia.